Math, asked by manasshenkar2569, 7 months ago

2) Solve : x + y = 11; 2x – 3y = 7​

Answers

Answered by sumitkumarsk7667093
0

Answer:

x + y = 11

= x = 11 - y ............(1)

we have the value of x .

Now put the value of x in

equation (2)

2x - 3y = 7

= 2 (11 - y) - 3y = 7 .....(from 1)

= 22 -2y - 3y = 7

= 22 - 5y = 7

= 22 - 7 = 5y

= 15 = 5y

= y = 3

we got the value of y

now put the value of in

equation (1)

x + 3 = 11

x = 11 - 3

x = 8

PLEASE LIKE & FOLLOW ME

HOPEFULLY THIS WILL HELP YOU A LOT

THANKS

Similar questions